HOSPITAL EDUCATORS' EXPECTATIONS OF ENTRY-LEVEL GRADUATE NURSES - Buteyn, Priscilla Navis (My University, 2010)
Nursing has recognized a dramatically changing practice environment. Graduate nurses are exposed to greater challenges and stresses than in previous decades. In a competitive healthcare delivery system, where cost conscious practices may limit orientation, graduate nurses are asked to perform competently, safely and proficiently within a short period of time. With increased scrutiny of nursing practices by regulatory and quality organizations, the pressure for quality without incident creates even greater demands on hospital educators and nursing staff to ensure competent and safe patient care. The expectations for graduate nurses entering the hospital or acute care setting may also be changing. New graduates who are unprepared for the realities and complexities of the practice setting have been leaving their entry-level positions within one year, creating vacancies and shortages and contributing to the high cost of recruitment and orientation (Halfer & Graf, 2006). The purpose of this study was to identify and describe the practice expectations hospital educators have of entry-level graduate nurses. Benner's (1984) Novice to Expert model provided the theoretical framework for this study. A non-experimental descriptive study was used to identify and describe the expectations hospital educators have of graduate nurses. A researcher created self administered questionnaire based on Benner's Framework, was sent out to hospital educators in Eastern Wisconsin from two large health systems. Demographic information was obtained. The survey consisted of questions surrounding perceived practice expectations that hospital nurse educators have of graduate nurses. Descriptive statistics were used to answer the research questions. By recognizing the expectations for graduate nurses entering the practice setting, this study helped identify the need to develop training and orientation programs that transition the graduate nurse successfully from novice to competent practice. The study found that externships or prolonged clinical experiences may facilitate early transition to a proficiency level of competent. Structured orientation programs lasting greater than four to six months, along with consistent mentors may improve retention of newly hired graduates. Demonstrating safe patient care practices, motivation to learn, communication skills, accountability, and respect for healthcare team members were identified as most important skills and attributes graduate nurses should possess. The study suggested that collaborative efforts between academic institutions and practice settings will strengthen and realistically prepare graduate nurses as they transition into the practice setting.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science in Nursing Nurse Educator
Keywords: Nursing psychological aspects; Interpersonal relationships; Nursing job satisfaction; Nursing practice